Effective Combinating of Wormhole Deadlock-free Routs - Valentin Olenev; Alexandr Karandashev (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2022)
Current paper discusses the problem of tracking of deadlock-free routes. A brief overview of existing software tools providing this functionality is given. A complete overview of the proposed software for building routes for given SpaceWire onboard networks is presented. The paper discusses the application of different existing methods for the choosing of the best route from the list of the deadlock-free routes. A brief overview of the methods for of choosing the best route according to the provided criteria is given. A new method for choosing of the best route and its modification is proposed. Authors provide the result of the methods application and the detailed comparison.